發展一個國小自然領域教學典範示例模式運用於師資培用聯盟 The Development of Science Teaching Plan Models Using in the Teacher Education Training League Program - 盧秀琴 Chow-Chin Lu (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2014)
教育部連續三年推動師資培用聯盟計畫，培育能教、會教且願意教的優良教師，本研究因應教育部，以焦點團體法發展5 個國小自然領域教學典範示例教案，師培教授使用這些教案進行臨床教學，由師資生、輔導教師觀摩後，開檢討會進行交流與修正；最後建置教學典範示例模式，提供於「師資培用聯盟自然領域學習中心」網站。研究結果發現：1.典範示例教案具備教材內容豐富而多元，科學化與生活實用性的特性，教學內容順序編排合宜而順暢；2.臨床教學以學童為中心，以體驗為主，讓學童自己去探索；師培教授能隨時檢核學童的學習，引導學童觀察重點，聚焦於學習重點；3.師培教授應先熟悉輔導教師的班級經營、師生互動模式，使用相 同模式在原來班級中臨床教學，學童較能接納而提升學習興趣。4.建置「師資培用聯盟自然領域學習中心」網站以展示教學典範示例教案，師資生使用這些教案參加教學演示競賽。 Ministry of Education has been propelling the teacher education training league program, which wishes to cultivate a teacher who’s able to teach, willing to teach and ready to teach. In this study, we lead the science education learning parts of this program. We design five teaching plans with the committees and teachers in the focus grouping meeting, then we actually teach the teaching plans in classes and review the teaching plans with science senior teachers and pre-service teachers in the meeting. After setting up the science teaching center website, we discuss how to promote the science teaching plan models in focus grouping meeting. The results showed that (1) Teaching plan models, which are basis on student experiences, not only have rich, diverse, scientific and practical teaching content, but also arranged in an appropriate teaching order. (2) When teaching the plans in class, not only the teacher led them in science observation, focus on the learning points and inspect their learning, but also the students can explore science by themselves. (3) To make sure that the students are able to accept and can enhance their interest in learning, clinical teaching teacher should find out what kind of class management their guidance teachers has used and how to interact with students before using the teaching plans in teaching. (4) To promote these teaching plan models, we establish a “Teacher education training league - Science teacher education learning center” website, and organize student teachers teaching competitions.